Can seasonal fire management reduce the risk of carbon loss from wildfires in a protected Guinea savanna?. Issue 11 (9th November 2022) - Awuah, Joana; Smith, Stuart W.; Speed, James D. M.; Graae, Bente J.
Abstract: Fire is fundamental to the functioning of tropical savannas and routinely used as a management tool. Shifting prescribed burning from later to earlier in the growing season has the potential to reduce greenhouse gas emissions. However, large uncertainties surround the impact of seasonal burning on longer term plant and soil carbon sequestration. In this study, we quantify ecosystem carbon storage across burn seasons and histories in a wet‐to‐mesic Guinea tropical savanna in Mole National Park, Ghana. Aboveground (plant and litter) and belowground (soil plus roots) carbon storage was quantified across four burning seasons and histories: recent (<3 years) early‐season burns, recent late‐season burns, old (>4 years) late‐season burns, and long‐unburned (>15 years) sites. We found that recent late‐season burns significantly lowered belowground carbon storage to a depth of 17 cm compared with all other burn seasons and histories. Belowground carbon was 1.2 kg C m −2, or 27% lower, for recent late‐season burns compared with prescribed early‐season burns. However, in older late‐season burns sites, belowground carbon "recovered" after 4–13 burn years to comparable storage as long‐unburned and early‐season burn sites. For most aboveground carbon pools, there was no significant difference in carbon storage across burn seasons and histories, except higher aboveground tree carbon in long‐unburned sites. We suggest that observed changes in belowground carbon are likely due to the turnover and production of root carbon. Prescribed early‐season burning is promoted to reduce greenhouse gas emissions and our findings affirm that early‐season burning has limited impact on plant and soil carbon stocks compared with long‐unburned sites. While early‐season burning regimes will have some patches that become late‐season wildfires, our results suggest on balance early‐season burning regimes are a low‐risk land management practice in reducing plant and soil carbon storage losses and sustaining a patch‐mosaicked landscape with multiple other ecosystem service benefits for savannas.